Systematic Review of Longitudinal Evidence and Methodologies for Research on Neighborhood Characteristics and Brain Health - Yvonne L. Michael; Araliya M. Senerat; Araliya M. Senerat; Channa Buxbaum; Ugonwa Ezeanyagu; Timothy M. Hughes; Kathleen M. Hayden; Julia Langmuir; Lilah M. Besser; Brisa Sánchez; Jana A. Hirsch; Jana A. Hirsch (Frontiers Media S.A., 2024)
Objective: Synthesize longitudinal research evaluating neighborhood environments and cognition to identify methodological approaches, findings, and gaps.Methods: Included studies evaluated associations between neighborhood and cognition longitudinally among adults >45 years (or mean age of 65 years) living in developed nations. We extracted data on sample characteristics, exposures, outcomes, methods, overall findings, and assessment of disparities.Results: Forty studies met our inclusion criteria. Most (65%) measured exposure only once and a majority focused on green space and/or blue space (water), neighborhood socioeconomic status, and recreation/physical activity facilities. Similarly, over half studied incident impairment, cognitive function or decline (70%), with one examining MRI (2.5%) or Alzheimer's disease (7.5%). While most studies used repeated measures analysis to evaluate changes in the brain health outcome (51%), many studies did not account for any type of correlation within neighborhoods (35%). Less than half evaluated effect modification by race/ethnicity, socioeconomic status, and/or sex/gender. Evidence was mixed and dependent on exposure or outcome assessed.Conclusion: Although longitudinal research evaluating neighborhood and cognitive decline has expanded, gaps remain in types of exposures, outcomes, analytic approaches, and sample diversity.